To Evaluate the Efficacy of Internet De-addiction Programme on Perceived Stress and Autonomic Functions in Young Adults - Jasrotia, Rajani Bala; Mishra, Anamika; Kanchan, Arvind; Kulshrestha, Sudhi; Ansari, Arshi (Nepal Journal of Neuroscience, 2023)
Internet addiction is characterized by excessive or poorly controlled preoccupations, urges or behaviors regarding computer use and internet access that lead to impairment or distress. The present study was conducted to evaluate the efficacy of internet de-addiction programme on stress and autonomic functions in young adults.500 young adults (age group 18-35 years), using smartphones and other gadget frequently were asked to answer Kimberley Young’s Internet addiction test (IAT) questionnaire. As per their responses 31 moderates to severely addicted to internet addiction (IAT score 64.51 ± 16.94) were motivated to participate in a comprehensive internet de-addiction programme, based on repeated sessions of psychological counselling and behavioral therapy as advised by an expert clinical Psychologist. Baseline and follow up (after 6 weeks) recording of Heart rate, Blood pressure, Perceived stress scale, IAT, Autonomic functions based on frequency domain HRV were done.There was significant increase in total power of HRV whereas significant reduction in LF/HF ratio, Perceived stress scores (PSS), Internet addiction scores and average daily mobile usage time after 6 weeks of follow up. It can be concluded from this study that after six weeks of comprehensive sessions based on cognitive behaviour therapy and guiding for self-help approach there were significant decrease in the total daily mobile usages time, internet addiction score, perceived stress score and also simultaneous improvement in symptho-vagal tone and overall autonomic health of participants.